In vivo neural isolation of the canine jejunoileum: temporal adaptation of enteric neuropeptides. Issue 11 (November 1991) - Nelson, D K; Sarr, M G; Go, V L
Abstract : This study was designed to assess temporal changes in concentrations of neuromodulatory peptides in plasma and gastrointestinal tissues after in vivo neural isolation of the entire canine jejunoileum. Fasting plasma and transmural biopsy specimens of stomach, duodenum, jejunum, ileum, and colon were obtained from the same dogs before and two, six, and 12 weeks after in situ neural isolation of the entire jejunoileum. Concentrations of vasoactive intestinal peptide, substance P, and neuropeptide Y were determined by quantitative radioimmunoassay. Tissue concentrations of vasoactive intestinal peptide and substance P in the neurally isolated regions increased progressively with time (198% and 217% average maximal increases, respectively), while fasting plasma concentrations changed little. Neuropeptide Y concentrations in plasma and in the jejunoileum were decreased (by 30% to 70%) at two weeks and remained decreased thereafter. Temporal changes in tissue neuropeptide concentrations occur in the neurally isolated jejunum and ileum. These adaptive changes in the neuropeptidergic innervation of the gut may play a role in the alterations in enteric function that occur after extrinsic denervation and after intestinal transplantation.